2022
DOI: 10.1186/s12958-022-00991-6
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates diabetic hyperglycaemia-induced impairment of Leydig cell steroidogenic function through activation of SIRT1 pathway

Abstract: Background Diabetes mellitus (DM)-related complications are important health problems worldwide. The underlying mechanisms for diabetic male subfertility/infertility are considerably complicated and need to be unveiled for therapeutic intervention. Melatonin treatment was investigated to assess the beneficial effects on injured steroidogenic function in DM due to its regulatory roles in mitochondria and autophagy. Methods Diabetic hyperglycaemia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previously, several studies have revealed that metabolic diseases such as obesity, diabetes, dyslipidemia, hypothyroidism, and hyperthyroidism can lead to excessive oxidative stress in the testes, while melatonin can vigorously potentiate endogenous anti-oxidant defense by upregulating SOD, GSH, and GPx ( 30 , 37 , 49 , 52 , 62 , 63 ). Melatonin can increase the testicular expression of nuclear factor erythroid 2–related factor 2 (Nrf2), which is a main transcription factor for many anti-oxidant genes and strengthens the anti-oxidant defense ( 64 ). Our meta-analysis showed that melatonin can markedly decrease the serum and tissue levels of MDA and significantly upregulate GSH; however, results were non-significant for other anti-oxidants such as SOD, CAT, and GPx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, several studies have revealed that metabolic diseases such as obesity, diabetes, dyslipidemia, hypothyroidism, and hyperthyroidism can lead to excessive oxidative stress in the testes, while melatonin can vigorously potentiate endogenous anti-oxidant defense by upregulating SOD, GSH, and GPx ( 30 , 37 , 49 , 52 , 62 , 63 ). Melatonin can increase the testicular expression of nuclear factor erythroid 2–related factor 2 (Nrf2), which is a main transcription factor for many anti-oxidant genes and strengthens the anti-oxidant defense ( 64 ). Our meta-analysis showed that melatonin can markedly decrease the serum and tissue levels of MDA and significantly upregulate GSH; however, results were non-significant for other anti-oxidants such as SOD, CAT, and GPx.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic perturbation suppressed AMPK/SIRT1 in the testicular tissue of diabetic mice and high-fat diet-fed mice, while treatment with melatonin markedly enhanced the AMP-activated protein kinase (AMPK)/SIRT1 pathway in their testis ( 30 , 64 ). Consistently, SIRT1 knockdown abolished the protective effects of melatonin on the detrimental effects of high glucose concentration on Leydig cells ( 64 ). Previously, it has been demonstrated that SIRT1 is a master regulator of metabolism and pivotal for spermatogenesis and spermatozoa differentiation ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles reported that SIRT1 could take part in the regulation of mitophagy by melatonin [ 52 , 61 ]. In diabetic rats or Leydig cells under high glucose, melatonin improved mitophagy defects to inhibit mitochondrial injury and oxidative stress by activating protein kinase (AMPK)/SIRT1 activity [ 62 ]. Above all, these results supported our findings that melatonin promotes PINK1/PARKIN-mediated mitophagy to inhibit H 2 O 2 -induced apoptosis and mitochondrial injury of bovine ovarian granulosa cells via a SIRT1-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins (SIRTs) are evolutionally-conserved family of regulatory proteins that function as NAD + -dependent class III histone deacetylases (HDACs), which is composed of seven histone deacetylases and ADP-ribosyltransferase proteins (SIRT1-7) in mammals [ 10 ]. As the most widely investigated member of the SIRT family, SIRT1 regulates cell biology and metabolism by deacetylating histones or other multiple cytoplasmic substrates and inhibiting proinflammatory kinases or regulating transcriptional factors, such as peroxisome proliferator-activated receptor-gamma co-activator 1α (PGC-1α), forkhead boxO3a (FoxO3a), nuclear factor kappa B p65 (NF-κB p65), p38 mitogen-activated protein kinase (p38 MAPK), and p300 [ [11] , [12] , [13] , [14] , [15] ]. A large amount of evidence has confirmed that SIRT1 plays an important role in the regulation of oxidative stress, inflammation, mitochondrial function, autophagy, apoptosis, neuroprotection and aging-related diseases [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%